Cost of Goods Sold Determination Analysis in Thrifting Business: The Case of @VINIZARA - Cahyaningtiyas, Niken; Aziz, M Taufik; Surono, Surono (CV. Strata Persada Academia, 2025)
The thrifting industry in Indonesia has experienced rapid growth, particularly among Generation Z consumers who prioritize affordability and sustainable fashion. This study investigates the cost of goods sold (COGS) determination process in a thrift-based retail enterprise, using @Vinizara in Cirebon as a case study. Employing a qualitative methodology with descriptive case study analysis, data were collected through in-depth interviews, direct observations, and financial document reviews. The research explores the cost calculation methods and pricing strategies used by the business, including cost-plus pricing, competitive pricing, and value-based pricing, while assessing their alignment with established cost accounting theories. The findings reveal that despite the absence of formal accounting systems, the applied pricing approach—based on practical intuition and market sensitivity—has enabled consistent inventory turnover and business sustainability. The study further highlights the importance of structured cost documentation and the use of appropriate COGS calculation methods to enhance pricing accuracy and operational efficiency. This research contributes theoretically to the literature on cost accounting in non-conventional retail and offers practical recommendations for thrift business owners and policymakers to improve financial literacy and pricing strategy implementation in MSMEs operating within the secondhand apparel sector.